Migratory gauntlets on oceanic islands: Watershed disturbance increases the cost of amphidromy. Issue 3 (11th February 2019) - Hain, Ernie F.; Moody, Kristine N.; Lamphere, Bradley A.; Nelson, Stacy A. C.; McIntyre, Peter B.; Gilliam, James F.; Blum, Michael J.
Abstract: Migratory fishes can be threatened by conditions encountered along dispersal pathways that impede access to feeding or breeding grounds. In this study, we tested the hypothesis that amphidromous fishes are equally or more sensitive to conditions along dispersal pathways than conditions in primary residential habitats. We did so by conducting distribution‐wide population surveys of all five amphidromous gobies native to the Hawaiian Islands to assess responses to in‐stream habitat, invasive species and watershed land use. We used Redundancy Analyses to assess whether goby densities varied according to local, downstream or upstream conditions. We found that population densities of the two non‐climbing species ( Eleotris sandwicensis, Stenogobius hawaiiensis ) varied according to local land use and local habitat conditions. Greater densities of E. sandwicensis also were found in watersheds with greater forest cover upstream of survey sites. Lower densities of two species that migrate farther inland ( Awaous stamineus, Sicyopterus stimpsoni ) were observed in watersheds with greater anthropogenic land use downstream or at the stream mouth. Population densities of E. sandwicensis and both Sicydiine species ( Lentipes concolor, S. stimpsoni ) also were lower when non‐native Poeciliids were locally present or present downstream in the watershed. These findings suggest that densities of native Hawaiian amphidromous fishes are equally or more sensitive to conditions along migratory pathways relative to conditions in primary residential habitats. Thus, alleviating pressures by removing invasive species and restoring habitat along dispersal pathways could be effective approaches to increasing densities of amphidromous species, especially those that migrate farther inland to higher elevations.